Faculty and Student Perceptions of Academic Integrity in Technology-Assisted Learning and Testing - Alessio, Helaine Mary; Messinger, Jeff D. (Frontiers in Education, 2021)
The recent COVID-19 pandemic presented challenges to faculty (Fac) and students (Stu) to uphold academic integrity when many classes transitioned from traditional to remote. This study compared Fac and Stu perceptions surrounding academic integrity when using technology assisted proctoring in online testing. METHODS: College Fac (N=150) and Stu (N=78) completed a survey about perceptions of academic integrity and use of proctoring software for online testing. Wilcoxon rank-sum tests were used to determine if there were differences in the distribution of agreement between students and faculty. RESULTS: Fac and Stu agreed maintaining academic integrity was a priority (93% v 94%), and that it is easier to cheat in online tests (81% v 83%). Responses differed on whether online proctoring software was effective at preventing academic dishonesty (23% of Fac v 42% of Stu disagreed). 53% of Fac and 70% of Stu perceived that online proctoring was an invasion of privacy. Only 7% of Stu and 49% of Fac perceived importance in having a policy about proctoring online tests, whether cheating in an academic setting is likely associated with cheating in a work setting (78% v 51%), and if given a choice, 46% of Fac and only 2% of Stu would choose to use proctoring software. Answers to open-ended questions identified feelings of stress and anxiety by Stu and concerns about privacy by Fac. CONCLUSION: Fac and Stu had similar perceptions of the importance of academic integrity and ease of cheating in online tests. They differed in perception of proctoring software’s effectiveness in deterring cheating, choosing to give or take a proctored online test, and having a policy in place. Policies on technology-assisted online testing should be developed with faculty and student input to address student concerns of privacy, anxiety, and stress and uphold academic integrity.